PENGARUH CD INTERAKTIF PADA MATERI SISTEM PERNAPASAN TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS XI SEMESTER II TAHUN PEMBELAJARAN 2013/2014 DI SMAN 5 PADANG - Komisa, Komisa; Nurhadi, Nurhadi; Maharani, Ade Dewi (Pendidikan Biologi, 2014)
ABSTRACTÂ Problems that occur in the learning process are low of studentâs biology achievement it was proved by students KKM that below 83 thase problems happens since some factor. One of the factor is media, media that used by the teacher are whiteboard, marker, chart, and power point. So that it is important for teacher to find out new media to overcome that problem. The aim of this study is to determine the effect of instructional media Interactive CD in human Respiratory System material toward studentâs motivation and biology achievement. The design of this research is an experimental study it used Randomized Control Group Posttest Only Design. The result of this research can be seen from studentâs biology score between experiments and control class87,97 and 79,37. Then, data analysis was performed by t tes (4,53) > t table (1,66) which means H1, is accepted. It can be concluded that Interactive CD can be improve studentâs motivation and biology achievement.Â